From Faith to Fun the Secularisation of Humour. - Heddendorf, Russell (Havertown : The Lutterworth Press, 2014)
Abraham and Sarah were presented with a paradox when God told them they would have a son in their old age. Paradox in the Old Testament plays an important part in the dialogue between God and the Jews. In the New Testament, paradox is prominent in Jesus' teaching and helps to explain the Christian understanding of salvation. Today paradox arises when religious meaning of traditional culture conflicts with secular meaning of modern culture. Heddendorf argues that a subversive quality in humour gradually replaces traditional values with new cultural meanings. The resulting humour becomes a subst.
Front cover; Title Page; Copyright Page; Contents; Dedication; Acknowledgments; Introduction; 1. Enter Isaac!; 2. The Power of Paradox; 3. The Technique of Humor; 4. And God Laughed; 5. Jewish Joy; 6. The Therapeutic Trend; 7. The Fun Factor; 8. Secular Fun; 9. Sacred Fun; 10. From Fun to Faith; 11. Conclusion; Bibliography; Back cover.
Print version record.
Master record variable field(s) change: 072
Keywords: Wit and humor -- Religious aspects -- Christianity; Christianity and culture; Christianity -- Social aspects; Secularism; Secularization (Theology); Popular culture -- Religious aspects -- Christianity; Christianity -- Social aspects; Christianity and culture; Popular culture -- Religious aspects -- Christianity; Secularism; Secularization (Theology); Wit and humor -- Religious aspects -- Christianity; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Christianity and culture; Christianity -- Social aspects; Popular culture -- Religious aspects -- Christianity; Secularism; Secularization (Theology); Wit and humor -- Religious aspects -- Christianity; RELIGION / Faith; Electronic books